Study on Knowledge -based Intelligent Fault Diagnosis of Hydraulic System - Xuexia Liu (Institute of Advanced Engineering and Science, 2012)
A general framework of hydraulic fault diagnosis system was studied. It consisted of equipment knowledge bases, real-time databases, fusion reasoning module, knowledge acquisition module and so on. A tree-structure model of fault knowledge was established. Fault nodes knowledge was encapsulated by object-oriented technique. Complete knowledge bases were made including fault bases and diagnosis bases. It could describe the fault positions, the structure of fault, cause-symptom relationships, diagnosis principles and other knowledge. Taking the fault of left and right lifting oil cylinder out of sync for example, the diagnostic results show that the methods were effective. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1637